IS THERE A WEEKEND EFFECT IN EUROPE? AN ANALYSIS OF DAILY RETURNS, NON-TRADING RETURNS, AND TRADING RETURNS - William Compton (Global Business and Finance Review, 2004)
This paper examines the stock markets o f eight European countries for recent evidence o f a weekend effect where Monday s return is significantly less than the re. ·t o f the week. We further decompose daily returns into non-trading periods (close-to-open) and trading periods (open-to-close) and test those return series using both parametric and non-parametric tests to address methodological problems identified in earlier studies. While are unable to find a weekend effect in European stock markets. While one major study uncovered a unique twist to the weekend effect in non-trading returns in the US stock market. we find no such unique twist tn the European stock markets.